Kiat Memilih Seorang Pemimpin dalam Konteks Hadis - Ali Mohtarom; Syaifullah (Fakultas Agama Islam Universitas Yudharta Pasuruan, 2024)
Literacy discussion on democracy in the context of hadith concludes that the selection and responsibilities of leaders need to consider several criteria. A qualitative literature study analyzing data highlights the importance of leaders' character, competence, and trustworthiness. In this context, an ideal leader is one with Qurayshi character, capable of governing, affiliating, mobilizing the masses, being economically adept, and exhibiting courtesy. The appointment of leaders should be based on the principle of consultation, with support and aspirations from the community. Leaders loved by the people and who love their people should be shielded from criticism, curses, and killings, although they must remain critical. The main conclusion is that leadership positions will only be honorable and successful if held by individuals with rights, perform their duties correctly, and are not discredited